PENGARUH DANA PIHAK KETIGA, NON PERFORMING LOAN DAN INFLASI TERHADAP KREDIT YANG DISALURKAN OLEH LPD KABUPATEN BADUNG PERIODE TAHUN 2008 - 2012 - Sariasih, Ni Wayan; Dewi, Made Rusmala (E-Jurnal Manajemen, 2014)
ABSTRACT   LPD existence in the area can provide socioeconomic effect is very large for the weak in rural communities in general accordance with the function and purpose as a financial institution that collects funds from the public and channel them back in the form of loans . The purpose of this study was to determine the effect of Third Party Funds , Non Performing Loan ( NPL ) , and inflation simultaneously and partially and which variables are the most dominant influence on the amount of loans extended by LPD Badung regency period 2008-2012 . By using multiple linear analysis techniques menunnjukkan that simultaneously deposits , non -performing loans , and inflation significantly influence lending by LPD Badung regency . In parcial third-party funds and non -performing loans and the positive effect singnifikan while inflation has negative and not significant to the loans extended by the LPD Badung regency period 2008-2012 . The most dominant variables affect lending LPD Badung is variable deposits. Keywords : Number of loans disbursed , Third Party Funds , Non Performing Loan( NPL ) , and inflation
Keywords: Number of loans disbursed , Third Party Funds , Non Performing Loan( NPL ) , and inflation